Classification of Zagros earthquakes based on focal mechanism - DELOUEI, Mehdi Nouri; GHEITANCHI, Mohammad-Reza (Contributions to Geophysics and Geodesy, 2021)
The Zagros suture zone is seismically active region in Iranian plateau. This region is of high importance in terms of seismicity, since it is a vast and populated region and in recent years the earthquakes with high intensities have frequently occurred and have caused extensive destruction and heavy human loss. The study of the focal mechanism is very important in understanding the seismotectonic characteristics. Focal mechanisms of Zagros were collected over a period of 20 years and they were classified by FMC software. Seven groups were considered for the type of faulting and Zagros was divided into three zones. For each zone, the frequency percentage of each group of faults was determined. The most of faulting are of the reverse and compression type with the strike-slip component. Finally, the role of nodal plane selection in determining the type of faulting was discussed and it was found that the selection of each nodal plane in determining the type of faulting has the same result.